(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
As the marine renewable energy sector expands, assessing the potential environmental impacts of wave energy converters (WECs) becomes increasingly important. Wave Swell Energy deployed the UniWave200 WEC from January 2021 to March 2023 at Grassy, King Island, Australia. The UniWave200 is a 13.6 m wide (alongshore) by 22.1 m long (cross-shore) concrete oscillating water column WEC that sits on the seabed, generating renewable energy via a unidirectional turbine above the surface. The UniWave200 WEC was deployed at depths of 4 to 6 metres, approximately 80 to 120 metres offshore at the eastern end of Grassy Beach. This demonstration project provided a unique opportunity to investigate the effect of a nearshore WEC on beach morphodynamics (e.g., shoreline change). Satellite-derived shoreline data was used to measure shoreline changes at Grassy throughout the WEC deployment (2021 to 2023) to assess the influence of the WEC on beach width. Early results showed that by February 2022, the beach had widened by approximately 25 metres in the lee of the WEC, compared to an average shoreline retreat of 1 metre along the entire beach and up to 22 metres of retreat at the western end of the beach. However, previous analysis of natural variability at Grassy from 1987 to 2021 showed that the shoreline position regularly widened by approximately 13 to 14 metres from austral winter (June, July, August) to summer (December, January, February) at the eastern end of Grassy Beach, due to seasonal beach rotation resulting from a reduction in offshore wave energy (Thompson et al., 2023). Therefore, the observed beach widening in the lee of the WEC may be linked to natural processes rather than the influence of the WEC device. Further investigation is underway using the satellite-derived shoreline dataset to develop a more detailed understanding of the impact of the UniWave200 on beach morphology compared to natural variability. These results have significant implications for the future of wave energy in coastal waters and the viability of nearshore WECs as coastal protection structures (similar to offshore breakwaters or artificial reefs). The potential impact of WECs on beach and surf amenity will also be discussed. This study highlights the importance of long-term coastal monitoring at future deployment sites to ensure that the impacts of WECs on coastal dynamics are well understood.